Pengaruh Kinerja Keuangan Perusahaan terhadap Return Saham (Studi pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia) - Aisjah, Siti; Sugiarti; Surachman (Jurnal Aplikasi Manajemen, 2015)
This study aims to examine and analyze the effect of variable current ratio, Debt toEquity Ratio, Return on Equity and Earning per Share to the Stock Return, using a quantitativeapproach with the Analysis Regression method. The population of this study is manufacturingcompanies listed in Indonesia Stock Exchange that pay dividend continuously forthe period 2009-2012. The population numbers are 28 companies that are observed withina period of 3 years, in order to obtain a total of 84 observations. The results showed that thevariable current ratio is a significant negative effect on stock returns. While the variableDebt to Equity Ratio is not significant negative effect on stock returns, and variable positiveReturn on Equity no significant effect on stock returns and variables Earning Per Share isnot significant negative effect on stock returns.